Explaining the fall of socioeconomic inequality in childhood stunting in Indonesia - Muhammad Fikru Rizal; Eddy van Doorslaer (Elsevier, 2019)
In spite of the enormous economic progress and development witnessed in Indonesia in the last few decades, still more than 30% of Indonesian children under the age of five suffer from stunting, or low height for age. This concern is exacerbated by the fact that stunting remains more concentrated among the poorer households, leading to further intergenerational transmission of poverty and ill health.We examine recent trends in the evolution of the prevalence of childhood stunting and severe stunting, its socioeconomic inequality and the factors that appear to have contributed to these developments. Using the two most recent waves of the Indonesia Family Life Survey (IFLS), we study the changes in the prevalence of (severe) stunting between 2007 and 2014 for children aged 0-59 months and their socioeconomic-inequality using the Erreygers Concentration Index (EI) and its regression-based decomposition.We find a significant drop in the rate of severe stunting but not in stunting, as well as a significant reduction in the degree of absolute inequality of stunting. A decomposition analysis shows that household wealth, maternal education, institutional delivery, and availability of adequate sanitation contribute most to socioeconomic inequality in under-five stunting. Further analysis of the change in inequality over time indicates that the reduction in the association of wealth with stunting and a substantial improvement of health care access of the poor (as proxied by immunizations and institutional deliveries) play the most important role in narrowing the stunting gap between richer and poorer kids.General economic growth, poverty reduction, and implementation of pro-poor health and social programs during the studied period such as the expansion of health insurance coverage for the poor (Jamkesmas) and Conditional Cash Transfer program (Program Keluarga Harapan, PKH) are some plausible explanations of the observed result. Keywords: Health inequality, Decomposition analysis, Indonesia, Stunting, Malnutrition